Kontrol Struktur Geologi terhadap Sebaran Skis Grafit di Perbukitan Jiwo Timur, Bayat, Klaten, Jawa Tengah - Kurniawan, Sandi; Rizqi, Al Hussein Flowers; Audrey, Vivi Fistina; Wijaya, Naufal Arya (Retii, 2023)
The construction of the Jogja - Solo toll road has incised piles of metamorphic rock that have just been exposed and can be used as research studies. A chunk of skis is found in a hillside fill in the East Jiwo area east of the Dengkeng river. As for specific research studies regarding graphite skis, it has never been studied clearly either in terms of its distribution or rock composition. This study covers an area where there is a distribution of graphite-skis lithology in the East Jiwo hills. The research areas are in Kebon Village and Gunung Gajah Village, Bayat District, Klaten Regency, Central Java. The aim of the study was to examine the lithology of graphite skies in detail using petrographic incisions and to interpret the geological structures that control the distribution of graphite skis in the study area. The research method includes field study stages that focus on collecting lithology, stratigraphy and geological structure data. Rock sampling is used in petrographic analysis. Retrieval of geological structure data includes data collection on foliation, joints, straightness, and drag faults and minor faults. The results of the geological structure analysis will provide an overview of the main stress directions that control the study area. The lithology of Kebon Village and Gununggajah Village was composed by Graphite Skis and Graphite Skis – Mika. The influence of geological structure controls the presence of graphite skis with the (Reverse Left Slip Fault) and Down-Right Fault (Normal Right Slip Fault). The two faults are thought to have formed simultaneously with the formation of the second-order Dengkeng fault.